Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Chrysidoidea, Bethylidae - Gadallah, Neveen S.; Azevedo, Celso O.; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Bethylidae is provided here. The list includes 29 identified valid species in 25 genera and five subfamilies: Bethylinae (2 genera, 0 species), Epyrinae (5 genera, 8 species), Mesitiinae (7 genera, 13 species), Pristocerinae (5 genus, 1 species) and Scleroderminae (6 genera, 7 species). Distributions, both on the Peninsula and extra-limital, are provided for each species; 17 species (59%) are endemic to the Arabian Peninsula.